Revitalizing The Role of Family in Children's Education - Abdullah Thahir; Munir Yusuf; Abd. Gafur Yusuf (Didaktika: Jurnal Kependidikan, 2022)
The advancement of communication and information technology has dramatically influenced both positive and negative influences, especially on children. Therefore, parents must educate their children well, not negatively, to influence the advancement of communication and information technology. Thus, as primary educators, parents must understand how to provide their children with the best education. The best education is to instil religious values in children from an early age, so the first and foremost thing to give this education is parents at home by setting a good example so that they can stick in the child's heart throughout his life.